Two-dimensional deformation in a thermoelastic solid with microtemperatures subjected to an internal heat source - Ailawalia, Praveen; Budhiraja, S.; Singh, J. (Zielona Góra: Uniwersytet Zielonogórski)
The purpose of this paper is to study the two dimensional deformation in a generalized thermoelastic medium with microtemperatures having an internal heat source subjected to a mechanical force. The force is acting along the interface of generalized thermoelastic half space and generalized thermoelastic half space with microtemperatures having an internal heat source. The normal mode analysis has been applied to obtain the exact expressions for the considered variables. The effect of internal heat source and microtemperatures on the above components has been depicted graphically.
Keywords: thermoelasticity; internal heat source; normal-mode; microtemperatures